Modeling, Control, and Simulation of a Solar Hydrogen/Fuel Cell Hybrid Energy System for Grid-Connected Applications. (4th April 2013) - Lajnef, Tourkia; Abid, Slim; Ammous, Anis
Abstract : Different energy sources and converters need to be integrated with each other for extended usage of alternative energy, in order to meet sustained load demands during various weather conditions. The objective of this paper is to associate photovoltaic generators, fuel cells, and electrolysers. Here, to sustain the power demand and solve the energy storage problem, electrical energy can be stored in the form of hydrogen. By using an electrolyser, hydrogen can be generated and stored for future use. The hydrogen produced by the electrolyser using PV power is used in the FC system and acts as an energy buffer. Thus, the effects of reduction and even the absence of the available power from the PV system can be easily tackled. Modeling and simulations are performed using MATLAB/Simulink and SimPowerSystems packages and results are presented to verify the effectiveness of the proposed system.